2005
DOI: 10.1007/s00221-005-2335-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying brain regions for integrative sensorimotor processing with ankle movements

Abstract: The objective of this study was to define cortical and subcortical structures activated during both active and passive movements of the ankle, which have a fundamental role in the physiology of locomotion, to improve our understanding of brain sensorimotor integration. Sixteen healthy subjects, all right-foot dominant, performed a dorsi-plantar flexion task of the foot using a custom-made wooden manipulandum, which enabled measurements of the movement amplitude. All subjects underwent a training session, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
106
4
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 35 publications
17
106
4
3
Order By: Relevance
“…PLMs are active periodic movements, and the pattern of brain activation resembles that reported during dorsiflexion-plantar flexion of the foot. 33 In agreement with the present study, a previous fMRI study performed on patients with RLS during combined PLMs and SLD demonstrated activation of the thalamus. 10 The thalamus is an intermediate gateway for sensory input according to cognitive requirements.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…PLMs are active periodic movements, and the pattern of brain activation resembles that reported during dorsiflexion-plantar flexion of the foot. 33 In agreement with the present study, a previous fMRI study performed on patients with RLS during combined PLMs and SLD demonstrated activation of the thalamus. 10 The thalamus is an intermediate gateway for sensory input according to cognitive requirements.…”
Section: Discussionsupporting
confidence: 93%
“…47 The left pars opercularis has been previously suggested to maintain and establish a task-set switching and is active during alternating movements. 33 The inability of patients with RLS to control their PLMs is consistent with a weak endogenous control, which may be associated with activation of the left pars opercularis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared to the patients, activation in the HVs extended more anteriorly into the precentral gyrus and also included inferior parietal areas. Generally, these activation patterns are in line with previous evidence on the functional neuroanatomical correlates of passive movement (Ciccarelli et al, 2005;Guzzetta et al, 2007;Naito et al, 1999;Naito et al, 2002;Weiller et al, 1996) and the assumption that the afferent feedback produced by passive movement not only targets somatosensory but also motor areas (Dechaumont-Palacin et al, 2008;Fetz et al, 1980;Lemon, 1999).…”
Section: Passive Movementsupporting
confidence: 90%
“…While functional neuroimaging has been utilized to examine the brain areas during static (isometric) (Newton et al 2008) or dynamic movements of a single leg (Ciccarelli et al 2005;Debaere et al 2001;Mehta et al 2012;Trinastic et al 2010), no previous studies have attempted to determine the additional brain areas required to coordinate simultaneous bilateral leg movements.…”
Section: Introductionmentioning
confidence: 99%